PENGARUH MODEL FLIPPED CLASSROOM DAN ENRICHED VIRTUAL TERHADAP HASIL BELAJAR KOGNITIF - Febriyana Munika Sari; Sri Sumaryati; Jaryanto Jaryanto (Jurnal Pengembangan Pendidikan Akuntansi dan Keuangan (JPPAK), 2022)
Abstract This study aims to determine (1) the effect of the flipped classroom learning model on the cognitive learning outcomes of institutional accounting practicum on accounting students, (2) the effect of the virtual enriched learning model on the cognitive learning outcomes of institutional accounting practicum on accounting students, and (3) the different effects of the flipped classroom and enriched virtual learning model on the cognitive learning outcomes of institutional accounting practicum on accounting students. This study uses a Quasy Experiment design (Nonequivaleent Control Group Design). The study population was students of accounting and financial institutions, and a sample were taken using cluster random sampling technique. The data analysis technique used paired sample t – test and independent sample t – test. The results of this study are. First, there is the effect of the flipped classroom model on the cognitive learning outcomes, which is indicated by the results of Sig < 0.05 (0.000 < 0.05). Second, there is an effect of the enriched virtual model on the cognitive learning outcomes, which is indicated by the results of Sig < 0.05 (0.000 < 0.05). Third, there is difference in the effect of the flipped classroom and enriched virtual model on the cognitive learning outcomes, which is indicated by the results of Sig < 0.05 (0.004 < 0.05). Therefore, it can be concluded that the flipped classroom and the enriched virtual model can both improve cognitive learning outcomes but with different level of increase. Keywords: Flipped classroom, enriched virtual, cognitive learning outcomes.  Abstrak Penelitian ini bertujuan untuk mengetahui (1) pengaruh model flipped classroom terhadap hasil belajar kognitif praktikum akuntansi lembaga pada siswa akuntansi, (2) pengaruh model enriched virtual terhadap hasil belajar kognitif praktikum akuntansi lembaga pada siswa akuntansi, dan (3) perbedaan pengaruh model flipped classroom dan enriched virtual terhadap hasil belajar kognitif praktikum akuntansi lembaga pada siswa akuntansi. Penelitian ini menggunakan desain Quasy Experiment (Nonequivalent Control Group Design). Populasi penelitian adalah siswa akuntansi dan keuangan lembaga, dan sampel diambil menggunakan teknik cluster random sampling. Teknik analisis data menggunakan uji paired sample t – test dan uji independent sample t – test. Hasil penelitian ini adalah. Pertama, terdapat pengaruh model flipped classroom terhadap hasil belajar kognitif, yang ditunjukkan dengan hasil Sig < 0,05 (0,000 < 0,05). Kedua, terdapat pengaruh model enriched virtual terhadap hasil belajar kognitif, yang ditunjukkan dengan hasil Sig < 0,05 (0,000 < 0,05). Ketiga, terdapat perbedaan pengaruh model flipped classroom dan enriched virtual terhadap hasil belajar kognitif, yang ditunjukkan dengan dengan hasil Sig < 0.05 (0,004 < 0,05). Oleh karena itu, dapat disimpulkan bahwa model flipped classroom dan enriched virtual sama – sama dapat meningkatkan hasil belajar kognitif tetapi dengan tingkat peningkatan yang berbeda. Kata Kunci: Flipped classroom, enriched virtual, hasil belajar kognitif.